Assessing divergent SST behavior during the last 21 ka derived from alkenones and G. ruber‐Mg/Ca in the equatorial Pacific. (30th June 2014) - Timmermann, Axel; Sachs, Julian; Timm, Oliver Elison
Abstract Equatorial Pacific SST reconstructions derived from Mg/Ca ratios in planktonic foraminifera Globigerinoides ruber and from alkenone‐producing coccolithophorids record different trends throughout the Holocene and the last deglaciation. We set forth the hypothesis that their diverging behavior may be related to different seasonal sensitivities which result from the annually varying production rates of alkenone‐producing coccolithophorids and of G. ruber. Using a series of transient paleoclimate model simulations forced with the time‐varying forcing history over the last 21 ka, a good qualitative agreement is found between simulated boreal winter temperatures and alkenone‐SST reconstructions as well as between simulated boreal summer temperatures and reconstructed Mg/Ca‐based SST variations. Pronounced features in the reconstructions that can be readily explained by the conjectured seasonal biases include the mismatch in middle‐to‐late Holocene temperature trends and the different onsets of deglacial climate change in the eastern equatorial Pacific. The analysis presented here further suggests that through combinations of Mg/Ca and alkenone SST reconstructions information can be gained on annual mean temperature changes and the amplitude of the seasonal cycle in SST. Our study concludes by discussing potential weaknesses of the proposed model‐derived seasonal bias interpretation of tropical Pacific SST proxies in terms of present‐day core‐top data, sediment trap studies, and satellite‐based observations of chlorophyll.